BURHANI DAN BAYANI DALAM DIALEKTIKA ILMU MENUJU EPISTEMOLOGI ISLAM YANG TRANSFORMATIF: - - Lailatul Zuhriyah; Angellita Salsabila Prasidha (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
The Islamic epistemological model has so far been dominated by the bayani (textual) and burhani (rational) approaches, which are often positioned in a dichotomous manner. In the contemporary socio-religious context, a single approach has proven to be inadequate to respond to the complexity of the reality of Muslims. This article explores the potential for integrating the two models as a foundation for developing a transformative Islamic epistemology, one that is not only normative but also contextual and offers solutions to the challenges of the present era. Through a qualitative approach with critical literature studies, it was found that the integration of Burhani and Bayani can strengthen the position of Islam as a religion that is intellectually and practically relevant. This study demonstrates that the synergy between reason and text creates space for the emergence of a more inclusive, adaptive, and liberating Islamic epistemology.